A Study of the Involvement of NCATE Institutions in the Support of Beginning Teachers - Ishler, Peggy F.; Selke, Mary J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This study examined higher education institutions' compliance with Standard IIB, Criterion #35 of the National Council for Accreditation of Teacher Education (NCATE), which focuses on arrangements the teacher education program has made with school districts to provide assistance to its graduates who are first year teachers. Data were obtained from reports prepared for accreditation reviews at 87 institutions. Fifty-eight of the institutions met Standard IIB with no weaknesses in criterion #35. Nineteen institutions met the standard, but with weakness cited in criterion #35. Ten institutions did not pass the standard; seven of these were cited for weakness in criterion #35. Forms of support for beginning educators included faculty conferring with graduates informally, formal mentors from colleges or universities working with beginning teachers, and formal mentors provided by school districts. Institutions that provided support only on an informal, unstructured basis or who sent letters to districts or graduates offering help were not assessed to have met criterion #35. Comparison with results of a 1987 study indicates that many NCATE institutions are taking an active role in teacher induction. The paper concludes that the socialization of beginning educators needs to reinforce teacher education program outcomes--and those outcomes need to be continually examined within the crucible of practice. (Contains 12 references.) (JDD)
ERIC Note: Paper presented at the National Meeting of the Association of Teacher Educators (Atlanta, GA, February 1994).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Accreditation (Institutions); Beginning Teacher Induction; Beginning Teachers; College Role; College School Cooperation; Educational Responsibility; Elementary Secondary Education; Higher Education; Institutional Evaluation; Program Development; Teacher Education Programs; National Council for Accreditation of Teacher Educ; Speeches/Meeting Papers; Reports, Research